Prarancangan Pabrik MTBE (Metil Tertiary Butil Eter) Dari Metanol Dengan Disain Alat Utama Menara Destilasi Pemisahan Metanol Dan TBA (T-102) - Zikir Akbar Kemala; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The increasing number of motorized vehicles is not matched by proper waste emission processing, which has a negative impact on the environment in the form of air pollution. This is a result of the incomplete combustion process so that the number of pollutants produced is increasing. One way to reduce the occurrence of incomplete combustion is by increasing the value of the octane number in motor vehicle fuel oil with additives that can increase the octane number such as methyl tert butyl ether (MTBE). MTBE production process is carried out by reacting the feed in the form of methanol with isobutene and the obtained production capacity is 180,000 tons / year. In the design of the distillation tower for the separation of methanol and Tertiary Butyl alcohol (TBA), the feed temperature, tower top and bottom of the tower were 333 K, 298 K and 328 K. The feed, distillate and bottom flow rates were 11,858 kg / hour, 10,644 kg, respectively. / hour and 1,214 kg / hour. The tower diameter is 2.27 m, with a spacing tray of 0.45 m, and the number of trays (without a reboiler) is 28. The type of flow that occurs inside the tower is a double pass with a total tower height of 13.77 m. The main equipment required is one reactor (fixed multitubular), one mixer (paddle), four for the distillation unit (sieve tray), three Heat Exchangers (one double pipe and two shell and tube), two heaters (shell and tube). , two coolers (double pipe), three centrifugal pumps, and five storage tanks (methanol, isobutene, MTBE, Butane and Water). The amount of Fixed Capital Investment (FCI) is 39,009,534. The amount of Direct Cost (DC) is 17,571,862 and Indirect Cost (IC) is 21,437,671. The Working Capital Investment (WCI) fee is 6,884,035 and the Total Capital Investment (TCI) fee is 45,893,569. The value of the Break Even Point (BEP) is 50%. The amount of Return On Investment (ROI) is 52%, Pay Out Time (POT) is 1.5 years, Shut Down Point (SDP) is 0.1% and the Internal Rate of Return (IRR) is 22.76%. The most sensitive factors that can affect the feasibility of this project are the selling price of the product and the volume of production. So that based on the analysis that has been done, it can be concluded that the factory is feasible to build. Keywords: Methyl tert butyl ether, tertiary butyl alcohol, total capital investment